Managing adoption by cultural development: Exploring the plant level effect of a company specific production system (XPS) in a Norwegian multinational company - Torbjørn Hekneby; Jonas A. Ingvaldsen; Jos Benders (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: 'Company Specific Production Systems' (XPS) aim to adopt 'best practice' across plants within a company. A pertinent issue in the literature involves the constraints in the possibilities of realising such an adoption. This paper addresses to what extent and how a Norwegian multinational succeeded in adopting the XPS in its local plants. Design/methodology/approach: A Brazilian, Chinese and Norwegian plant of a Norwegian electro-chemical company were studied from 2017 to 2019. Our data consist of the results of the plant's assessment performance program, combined with interviews and observations at different organizational levels. Findings: The MNC had largely managed to adopt the XPS in these plants. This was made possible by creating a strong corporate culture, shaping the managers' basic assumptions, and persuading lower-level management and operators to adopt the improvement programme. The corporate culture was the result of several initiatives including the deployment of different HRM practices, supported by top management teams and by using the Norwegian plant as a laboratory visited by global operators and managers. Originality/value: This paper is, to our knowledge, the first to study the actual use of an XPS intra-organizationally. It highlights the role of culture development and basic assumptions for achieving global adoption. Global improvement programmes require constant managerial attention and actions at several levels in order to be adopted globally.
Keywords: 650; Company-specific production systems (XPS); local adoption; cultural development; basic assumptions; Toyota production system